Factors associated with local herb use during pregnancy and labor among women in Kigoma region, Tanzania, 2014-2016 - R. Fukunaga; D. Morof; C. Blanton; A. Ruiz; G. Maro; F. Serbanescu (BMC, 2020)
Abstract Background Despite research suggesting an association between certain herb use during pregnancy and delivery and postnatal complications, herbs are still commonly used among pregnant women in sub-Sahara Africa (SSA). This study examines the factors and characteristics of women using local herbs during pregnancy and/or labor, and the associations between local herb use and postnatal complications in Kigoma, Tanzania. Methods We analyzed data from the 2016 Kigoma Tanzania Reproductive Health Survey (RHS), a regionally representative, population-based survey of reproductive age women (15-49 years). We included information on each woman's most recent pregnancy resulting in a live birth during January 2014-September 2016. We calculated weighted prevalence estimates and used multivariable logistic regression to calculate adjusted odds ratios (aOR) and 95% confidence intervals (CI) for factors associated with use of local herbs during pregnancy and/or labor, as well as factors associated with postnatal complications. Results Of 3530 women, 10.9% (CI: 9.0-13.1) used local herbs during their last pregnancy and/or labor resulting in live birth. The most common reasons for taking local herbs included stomach pain (42.9%) and for the health of the child (25.5%). Adjusted odds of local herb use was higher for women reporting a home versus facility-based delivery (aOR: 1.6, CI: 1.1-2.2), having one versus three or more prior live births (aOR: 1.8, CI: 1.4-2.4), and having a household income in the lowest versus the highest wealth tercile (aOR: 1.4, CI: 1.1-1.9). Adjusted odds of postnatal complications were higher among women who used local herbs versus those who did not (aOR: 1.5, CI: 1.2-1.9), had four or more antenatal care visits versus fewer (aOR: 1.4, CI: 1.2-1.2), and were aged 25-34 (aOR: 1.1, CI: 1.0-1.3) and 35-49 (aOR: 1.3, CI: 1.0-1.6) versus < 25 years. Conclusions About one in ten women in Kigoma used local herbs during their most recent pregnancy and/or labor and had a high risk of postnatal complications. Health providers may consider screening pregnant women for herb use during antenatal and delivery care as well as provide information about any known risks of complications from herb use.